Mengapa public relations penting bagi industri perbankan? - Frasasti, Meilinda (Maliki Interdisciplinary Journal, 2025)
Public relations is a communication science that is built with several processes. The process must be done carefully because it is directly related to the wider community. Public relations are closely related to a company, one of which is in the banking world. Banking is a company engaged in finance, where its activities are collecting and channeling public funds and providing other services. This process involves the role of public relations in conveying information in the company, as well as helping to maintain the image, expand cooperation, build public trust. Achieving goals will provide great benefits for the company. The role of public relations in the banking industry extends beyond simply conveying information, but also serves as an effective communication bridge between the company and the public. Through a well-planned communication strategy, public relations can create a positive image, manage emerging issues, and increase customer loyalty. In the context of increasingly competitive banking industry, public relations serves as a crucial instrument for service differentiation and building a long-term reputation. Studies have shown that effective public relations practices contribute to increased public trust, expanded partnership networks, and supported company stability in the face of market dynamics and digital technology developments.